2022
DOI: 10.1111/jgh.15881
|View full text |Cite
|
Sign up to set email alerts
|

Serum qAnti‐HBc combined with ALT and HBsAg predicts significant hepatic inflammation in HBeAg‐positive immune active patients

Abstract: Author contributions: Junqi Niu and Qinglong Jin designed and supervised the study. Xiaomei Wang analyzed the data and drafted the manuscript. Xiuzhu Gao, Xiumei Chi, and Yazhe Guan acquired the data. Ruihong Wu and Hongqin Xu performed the statistical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While some studies report that qAnti-HBc levels were helpful in the prediction of moderate-to-severe inflammation in both HBeAg-positive and HBeAg-negative CHB phases, others indicate that this benefit is more exhibited in HBe-positive patients [ 19 , 44 , 47 ]. Most authors emphasise that qAnti-HBc alone is not enough to predict the inflammation grade accurately and that its combination with other biomarkers is desirable [ 44 , 45 , 47 , 49 ]. There is a conclusion from a recent study that combined qAnti-HBc, ALT, and HBsAg offer better performance in predicting significant liver inflammation than qAnti-HBc alone or in combination with only ALT [ 49 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies report that qAnti-HBc levels were helpful in the prediction of moderate-to-severe inflammation in both HBeAg-positive and HBeAg-negative CHB phases, others indicate that this benefit is more exhibited in HBe-positive patients [ 19 , 44 , 47 ]. Most authors emphasise that qAnti-HBc alone is not enough to predict the inflammation grade accurately and that its combination with other biomarkers is desirable [ 44 , 45 , 47 , 49 ]. There is a conclusion from a recent study that combined qAnti-HBc, ALT, and HBsAg offer better performance in predicting significant liver inflammation than qAnti-HBc alone or in combination with only ALT [ 49 ].…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
“…Most authors emphasise that qAnti-HBc alone is not enough to predict the inflammation grade accurately and that its combination with other biomarkers is desirable [ 44 , 45 , 47 , 49 ]. There is a conclusion from a recent study that combined qAnti-HBc, ALT, and HBsAg offer better performance in predicting significant liver inflammation than qAnti-HBc alone or in combination with only ALT [ 49 ]. According to a recent study, following the worsening of inflammation and progression of fibrosis through phases of CHB, qAnti-HBc levels were increasing slowly but constantly from HBeAg-positive to HBeAg-negative phases.…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies noted the positive correlation between serum ALT activity and qAnti-HBc in CHB patients, suggesting the latter may indicate hepatic inflammation [ 26 , 27 , 28 ]. Moreover, qAnti-HBc has been documented to correlate positively with the histological severity of hepatic inflammation determined by liver biopsy [ 28 , 29 , 30 ]. Interestingly, some studies have found that qAnti-HBc is also associated with fibrosis severity and can provide improved value for the performance of non-invasive indexes in combination with other parameters [ 31 , 32 , 33 ].…”
Section: The Qanti-hbc Levels In the Natural History Of Hbv Infectionmentioning
confidence: 99%